A method for preparing high-conductivity and high-strength copper-plated carbon fiber

Through ablation and oxidation of polyacrylonitrile-based carbon fibers and post-plating annealing treatment, the problems of insufficient conductivity and mechanical properties of copper-plated carbon fibers are solved, and the preparation of copper-plated carbon fibers with high conductivity and high strength is achieved.

CN115821340BActive Publication Date: 2025-01-07SHANDONG UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211573288.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-01-07
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

The existing copper-plated carbon fibers have insufficient electrical conductivity and mechanical properties, mainly due to the low plating defects and interface bonding strength during electroplating, resulting in unsatisfactory electrical conductivity and less obvious improvement in mechanical properties.

Method used

Polyacrylonitrile-based carbon fiber is used for ablation and oxidation treatment, and copper sulfate, sodium citrate, sodium tartrate and sodium dodecyl sulfate are added to the electroplating solution, and the copper plating carbon fiber is annealed after electroplating. Conductivity and mechanical properties.

Benefits of technology

Through annealing treatment, the copper plating layer is closely combined with carbon fiber, which reduces the contact resistance between the copper structure, significantly improves the conductivity and mechanical properties, reduces the defects and stress concentration points of the copper layer, and improves the overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115821340B_ABST
    Figure CN115821340B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-conductivity and high-strength copper-plated carbon fiber: 1) ablation, cleaning and drying of polyacrylonitrile-based carbon fiber to obtain surface-oxidized carbon fiber; 2) copper sulfate, sodium citrate, sodium tartrate, sodium dodecyl sulfate and water are mixed to prepare electroplating solution; 3) the surface-oxidized carbon fiber is used as a cathode and a copper sheet is used as an anode, electroplating is performed in the electroplating solution, and the surface is cleaned to neutrality with deionized water, and dried in a vacuum oven to obtain copper-plated carbon fiber; 4) the copper-plated carbon fiber is annealed and cooled under nitrogen protection. The invention performs surface ablation and oxidation treatment on the carbon fiber, so that the surface of the carbon fiber has a suitable roughness, improves the interface bonding force between the coating and the carbon fiber, and the annealing treatment solves the problems of poor coating quality, many defects and easy peeling when copper is used. After annealing, the coating is dense and uniform, the resistivity and porosity are reduced, the stress concentration points are reduced, and the mechanical properties are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to conductive fibers, and in particular to a method for preparing high-conductive and high-strength copper-plated carbon fibers. Background Art

[0002] Carbon fiber has the advantages of high strength, high modulus, low expansion coefficient, and low density, and is widely used in aerospace, automobiles, ships, sporting goods, medical equipment, and other fields. At the same time, conductive materials and electromagnetic shielding materials prepared using carbon fiber and its composite materials have the advantages of light weight and high strength, and have the potential to replace traditional metal materials. However, since carbon fiber is a non-metallic fiber, its resistivity is much higher than that of metal, which makes the conductivity and electromagnetic shielding effect of the material poor, so it is necessary to improve the conductivity of carbon fiber.

[0003] Carbon fiber metallization is an effective way to improve the conductivity of carbon fiber. Metallization can also solve the problem of poor wettability and compatibility between carbon fiber and metal matrix. Many researchers have used silver, copper, nickel, zinc, platinum and other metals to coat modified carbon fiber. Among them, copper has the advantages of low price and high conductivity, and is used more. At present, among many metallization processes, electroplating is one of the effective methods for preparing metallized carbon fiber.

[0004] The copper / carbon composite material prepared by electroplating and chemical plating modified carbon fiber has high adhesion to the carbon fiber. The copper-plated carbon fiber can also be used as a new type of conductor material. Compared with traditional metal conductors, it has the advantages of light weight, high mechanical strength, and large load capacity. However, the electroplating method also has some shortcomings. For example, the generation of gas and the incorporation of impurities during the electroplating process will cause obvious defects in the electroplated copper layer. The temperature is low when the coating is formed, the interface bonding strength is low, and the electroplated copper layer is loose and easy to peel off, resulting in unsatisfactory conductivity of the copper-plated carbon fiber and the improvement of mechanical properties is not as expected. Summary of the invention

[0005] Aiming at the problem that the coating defects of the existing copper-plated carbon fiber are obvious, resulting in the inability to achieve the expected conductivity and mechanical properties, the present invention provides a method for preparing high-conductivity and high-strength copper-plated carbon fiber, which comprises the following steps: 1) ablating polyacrylonitrile-based carbon fiber at 400-500° C. for 20-40 min, washing, and drying to obtain surface-oxidized carbon fiber; 2) mixing copper sulfate, sodium citrate, sodium tartrate, sodium dodecyl sulfate and water to prepare an electroplating solution; 3) using the surface-oxidized carbon fiber of step 1) as a cathode and a copper sheet as an anode, electroplating in the electroplating solution prepared in step 2), washing the electroplated carbon fiber with deionized water to neutrality, and drying in a vacuum oven to obtain copper-plated carbon fiber; 4) heating the copper-plated carbon fiber obtained in step 3) to 400-600° C. at 8-12° C. / min under nitrogen protection, annealing for 10-40 min, and cooling to obtain high-conductivity and high-strength copper-plated carbon fiber.

[0006] Carbon fiber can be divided into polyacrylonitrile-based carbon fiber, viscose-based carbon fiber and asphalt-based carbon fiber according to different raw materials. Among them, the comprehensive performance of viscose-based carbon fiber and asphalt-based carbon fiber is lower than that of polyacrylonitrile-based carbon fiber. The precursor of polyacrylonitrile-based carbon fiber can be accurately prepared into polyacrylonitrile with required indicators through a condition-controlled polymerization process. The obtained polyacrylonitrile has a high molecular weight and a narrow distribution. The carbon fiber obtained after carbonization has few molecular defects and excellent mechanical properties of the fiber. Therefore, the present invention adopts polyacrylonitrile-based carbon fiber for ablation. The specification of the polyacrylonitrile carbon fiber used is 6~12k, and the single fiber diameter is 4~10 μm.

[0007] Specifically, in the electroplating solution configured in step 2), the concentration of copper sulfate is controlled to be 50 g / L, the concentration of sodium citrate is 80-100 g / L, the concentration of sodium tartrate is 1-5 g / L, and the concentration of sodium dodecyl sulfate is 0.1-0.6 g / L; in step 3), the size of the copper sheet is 80×20×1 mm; the temperature of the electroplating solution is 30-60° C., and the electroplating voltage is 4-8 V.

[0008] The present invention performs surface ablation and oxidation treatment on the carbon fiber so that the carbon fiber surface has appropriate roughness, which is beneficial to improving the interface bonding force between the coating and the carbon fiber surface; the annealing treatment effectively solves the problems of poor coating quality, many defects, easy peeling, etc. when the carbon fiber is copper-plated; after annealing, the carbon fiber and the coating are tightly bonded, the coating is dense and uniform, the contact resistance between the copper tissues is reduced, a better conduction path is provided for electrons, the resistivity is reduced, and the conductivity is significantly improved compared with the unannealed copper-plated carbon fiber; after annealing, the porosity is reduced, the oxidation resistance of the copper-plated carbon fiber is improved, the defects of the copper layer are reduced after annealing, the stress concentration points are reduced, and the mechanical properties are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] FIG1 is a SEM image of carbon fiber before (a) and after (b) ablation in Example 1;

[0010] FIG2 is the full XPS spectra of carbon fiber before ablation (CF) and after ablation (Oxidized CF) in Example 1;

[0011] FIG3 is a C1s peak spectrum of carbon fiber before (a) and after (b) ablation in Example 1;

[0012] Figure 4 shows the stress response of carbon fiber before ablation (CF) and after ablation (Oxidized CF) in Example 1.

[0013] Variation curve (a) and strength and modulus bar graph (b);

[0014] FIG5 is a SEM image of the fiber surface of the copper-coated carbon fiber obtained in Example 1 before annealing (10 μm) and after annealing (5 μm);

[0015] FIG6 is a SEM image of the fiber surface of the copper-coated carbon fiber obtained in Example 2 before annealing (10 μm) and after annealing (5 μm);

[0016] FIG7 is an XRD spectrum of the copper-plated carbon fiber (CF-Cu) obtained in Comparative Example 1, the high-conductivity and high-strength copper-plated carbon fiber (CF-Cu annealed at 600°C) obtained in Example 1, the high-conductivity and high-strength copper-plated carbon fiber (CF-Cu annealed at 400°C) obtained in Example 2, and the high-conductivity and high-strength copper-plated carbon fiber (CF-Cu annealedat500°C) obtained in Example 3;

[0017] FIG8 is a graph of grain size and a histogram of electrical conductivity of the fibers of Comparative Example 1, Example 2, Example 3 and Example 1 from left to right;

[0018] FIG9 is a bar graph showing the strength and modulus of the ablated carbon fiber (1) of Example 1, the copper-coated carbon fiber (2) of Comparative Example 1, the high-conductivity and high-strength copper-coated carbon fiber (3) of Example 2, the high-conductivity and high-strength copper-coated carbon fiber (4) of Example 3, and the high-conductivity and high-strength copper-coated carbon fiber (5) of Example 1;

[0019] FIG10 shows stress-strain curves of the ablated carbon fiber (Oxidized CF) of Example 1, the copper-plated carbon fiber (CF-Cu) of Comparative Example 1, the high-conductivity and high-strength copper-plated carbon fiber (400°C) of Example 2, the high-conductivity and high-strength copper-plated carbon fiber (500°C) of Example 3, and the high-conductivity and high-strength copper-plated carbon fiber (600°C) of Example 1. DETAILED DESCRIPTION

[0020] The present invention is described below in conjunction with examples, which are only used to explain the present invention and are not used to limit the scope of the present invention.

[0021] 1. The raw materials used in the present invention are as follows:

[0022] 1. Polyacrylonitrile-based carbon fiber (12k monofilament) produced by Taiwan Plastics Industry Co., Ltd., the monofilament diameter of the fiber is about 7 μm, and it is not sized;

[0023] 2. Sodium tartrate and sodium citrate were analytical grade and produced by Komiou Chemical Reagent Co., Ltd.;

[0024] 3. Copper sulfate was of analytical grade and produced by Tianjin Yongda Chemical Reagent Co., Ltd.;

[0025] 4. Sodium dodecyl sulfate was of analytical grade and produced by Shanghai MacLean Biochemical Co., Ltd.;

[0026] 5. The anode is a copper plate with a purity of ≥99.9%, produced by Shenzhen Quanfu Metal Co., Ltd.

[0027] 2. The characterization equipment and detection method of the present invention are as follows:

[0028] 1. Use a field emission scanning electron microscope (SEM450 Nova Nano) to observe the morphology of carbon fiber, copper-coated carbon fiber, and annealed copper-coated carbon fiber;

[0029] 2. Use the attached energy dispersive spectrometer (EDS) to perform element analysis on the surface of copper-coated carbon fiber;

[0030] 3. The crystallographic properties of copper-coated carbon fiber and copper-coated carbon fiber after annealing were studied using X-ray diffractometer (XRD, Ultima IV);

[0031] 4. Use Thermo Fisher Scientific K-Alpha X-ray photoelectron spectrometer to study the surface elements and their relative contents of carbon fibers before and after oxidation treatment. The excitation light source is Al-Ka (1486.6 eV) and the jet voltage is 15 kV.

[0032] 5. Use a fiber strength and elongation tester (XQ-1A) to test the fiber breaking force. The test data uses the average value of 30 parallel samples. The test sample length is 20mm and the tensile speed is 5mm / min.

[0033] Example 1

[0034] A method for preparing high-conductivity and high-strength copper-plated carbon fiber comprises the following steps:

[0035] 1) The polyacrylonitrile-based carbon fiber was ablated at 450°C for 30 min, cleaned, and dried to obtain surface-oxidized carbon fiber;

[0036] 2) Add copper sulfate, sodium citrate, sodium tartrate and sodium dodecyl sulfate into water to prepare the electroplating solution, and control the concentration of copper sulfate to 50g / L, sodium citrate to 100g / L, sodium tartrate to 3g / L and sodium dodecyl sulfate to 0.5g / L;

[0037] 3) The carbon fiber with surface oxidation in step 1) is used as the cathode and the copper sheet with size of 80×20×1mm is used as the anode. The carbon fiber is electroplated in the electroplating solution prepared in step 2). The electroplating solution temperature is 40°C and the electroplating voltage is 5V. After electroplating for ten minutes, the electroplated carbon fiber is washed with deionized water until it is neutral, and dried in a vacuum oven at 60°C for 4h to obtain copper-plated carbon fiber.

[0038] 4) The copper-plated carbon fiber obtained in step 3) is heated to 600° C. at 10° C. / min and annealed for 20 min under nitrogen protection, and then cooled to obtain high-conductivity and high-strength copper-plated carbon fiber.

[0039] Example 2

[0040] A method for preparing high-conductivity and high-strength copper-plated carbon fiber comprises the following steps:

[0041] 1) The polyacrylonitrile-based carbon fiber was ablated at 500°C for 20 min, cleaned, and dried to obtain surface-oxidized carbon fiber;

[0042] 2) Add copper sulfate, sodium citrate, sodium tartrate and sodium dodecyl sulfate into water to prepare the electroplating solution, and control the concentration of copper sulfate to 50g / L, sodium citrate to 80g / L, sodium tartrate to 5g / L and sodium dodecyl sulfate to 0.6g / L;

[0043] 3) The carbon fiber with surface oxidation in step 1) is used as the cathode and the copper sheet with size of 80×20×1mm is used as the anode. The carbon fiber is electroplated in the electroplating solution prepared in step 2). The electroplating solution temperature is 60°C and the electroplating voltage is 8V. After electroplating for ten minutes, the electroplated carbon fiber is washed with deionized water until it is neutral, and dried in a vacuum oven at 60°C for 4h to obtain copper-plated carbon fiber.

[0044] 4) The copper-plated carbon fiber obtained in step 3) is heated to 400° C. at 8° C. / min and annealed for 15 min under nitrogen protection, and then cooled to obtain high-conductivity and high-strength copper-plated carbon fiber.

[0045] Example 3

[0046] A method for preparing high-conductivity and high-strength copper-plated carbon fiber comprises the following steps:

[0047] 1) The polyacrylonitrile-based carbon fiber was ablated at 400°C for 40 min, cleaned, and dried to obtain surface-oxidized carbon fiber;

[0048] 2) Add copper sulfate, sodium citrate, sodium tartrate and sodium dodecyl sulfate into water to prepare the electroplating solution, and control the concentration of copper sulfate to 50g / L, sodium citrate to 90g / L, sodium tartrate to 1g / L and sodium dodecyl sulfate to 0.1g / L;

[0049] 3) The carbon fiber with surface oxidation in step 1) is used as the cathode and the copper sheet with size of 80×20×1mm is used as the anode. The carbon fiber is electroplated in the electroplating solution prepared in step 2). The electroplating solution temperature is 50°C and the electroplating voltage is 4V. After electroplating for fifteen minutes, the electroplated carbon fiber is washed with deionized water until it is neutral, and dried in a vacuum oven at 60°C for 4h to obtain copper-plated carbon fiber.

[0050] 4) The copper-plated carbon fiber obtained in step 3) is heated to 500° C. at 12° C. / min and annealed for 30 min under nitrogen protection, and then cooled to obtain high-conductivity and high-strength copper-plated carbon fiber.

[0051] Comparative Example 1

[0052] The only difference from Example 1 is that the copper-plated carbon fiber obtained in step 3) is not subjected to annealing treatment.

[0053] Figure 1 is the SEM image of the carbon fiber before (a) and after (b) ablation in Example 1. The grooves on the surface of the carbon fiber after ablation are more obvious, the number increases, and grooves are generated. The roughness of the fiber surface increases. This rough surface will be beneficial to the mechanical interlocking of carbon fiber and copper and improve the interface bonding strength. Figure 2 is the XPS full spectrum of the carbon fiber before (CF) and after (Oxidized CF) ablation in Example 1. The element content of the carbon fiber surface is analyzed, as shown in Table 1.

[0054] Table 1. Relative content of surface elements of carbon fiber before ablation (CF) and after ablation (Oxidized CF) in Example 1

[0055] C1s (%) O1s (%) O1s / C1s CFs 86.78 13.43 15.48 Oxidized CFs 79.27 20.73 26.15

[0056] From the analysis results in Table 1, it can be seen that the surface elements of carbon fiber are mainly carbon and oxygen. After the carbon fiber is subjected to ablation and oxidation treatment, the concentration of O1s atoms increases significantly, from 13.43% to 20.73%, and O1s / C1s increases from 15.48 to 26.15.

[0057] Figure 3 is the C1s peak spectra of the carbon fiber before (a) and after (b) ablation in Example 1. It can be seen that the carbon in the untreated carbon fiber is present in the form of CC bonds at the highest level, and in the form of oxygen-containing functional groups such as -C=OH and COOH at a lower level. After oxidation treatment, the carbon content in the form of oxygen-containing functional groups such as -C=OH and COOH increases, and the types of oxygen-containing functional groups increase. The carbon content in different functional groups on the surface of the carbon fiber before and after ablation in Example 1 is shown in Table 2.

[0058] Table 2. Surface functional group content of carbon fiber before and after ablation in Example 1

[0059] C-C (%) -OH (%) COOH (%) -C=O (%) CFs 73.40 19.27 7.33 - Oxidized CFs 52.34 16.51 15.61 15.55

[0060] It can be seen from Table 2 that after ablation treatment, the CC content on the carbon fiber surface decreased by 21.06%, the C-OH content decreased by 2.76%, the -C=O content increased by 8.28%, and the COOH content increased by 15.55%. This shows that the air oxidation treatment has a good activation and modification effect on the carbon fiber, and oxidation generates oxygen-containing active functional groups such as -C=O and -COOH. These oxygen-containing functional groups can serve as active sites to promote the deposition of copper ions on the fiber surface and make the carbon fiber have good wettability and dispersibility in the solution.

[0061] Figure 4 shows the stress response of carbon fiber before ablation (CF) and after ablation (Oxidized CF) in Example 1.

[0062] The curve (a) and the strength and modulus bar graph (b) show that the mechanical properties of carbon fiber decrease slightly after oxidation treatment, but the decrease is not much. The single fiber strength of carbon fiber decreases from 4.41GPa to 4.2GPa, and the modulus decreases from 253.14GPa to 238.4GPa. This is because ablation deepens the grooves and grooves on the surface of carbon fiber, thereby increasing the stress concentration points on the fiber surface.

[0063] The copper and carbon fiber are mainly bonded by mechanical interlocking rather than chemical bonding, and the copper obtained by electroplating has a smaller grain size and higher porosity. The annealing process can eliminate defects and improve the quality of the coating, Figure 5 and Figure 6 The SEM images of the fiber surface of the copper-plated carbon fibers obtained in Example 1 and Example 2 before annealing (10 μm) and after annealing (5 μm) respectively show that after annealing, the copper particles fuse with each other, the copper layer becomes denser and smoother, the particle size increases significantly, and the copper plating effect of Example 1 is better.

[0064] FIG7 is an XRD spectrum of the copper-plated carbon fiber (CF-Cu) obtained in Comparative Example 1, the high-conductivity and high-strength copper-plated carbon fiber (CF-Cu annealed at 600°C) obtained in Example 1, the high-conductivity and high-strength copper-plated carbon fiber (CF-Cu annealed at 400°C) obtained in Example 2, and the high-conductivity and high-strength copper-plated carbon fiber (CF-Cu annealed at500°C) obtained in Example 3. There are three crystalline diffraction peaks at 2θ=43.4°, 50.5° and 74.2°, corresponding to the three crystal plane diffraction peaks of (111), (200) and (220), respectively, which is consistent with the face-centered cubic structure of metallic copper. After annealing the copper layer, the diffraction peak intensity is further increased, especially in Example 1. The diffraction peak intensity of the copper-plated carbon fiber after annealing at 600°C is nearly twice that of the copper layer in the unannealed state, and the grains grow preferentially in the (111) direction, indicating that the annealing treatment enhances the crystallinity and grain size of the copper layer.

[0065] According to the XRD results, the average grain size (Dp) of the electroplated Cu layer was calculated using formula (1):

[0066] Formula (1),

[0067] Where Dp is the average grain size, λ is the X-ray wavelength, β is the half-width (FWHM) intensity line in the diffraction curve, and θ is the Bragg angle.

[0068] The calculated results are shown in the graph in Figure 8. It can be seen that the grain size of the Cu layer increases with the increase of annealing temperature. The grain size of the unannealed Cu layer in the (111) direction is 10.4 nm, while the grain size of the annealed (600℃) sample increases to 22.7 nm.

[0069] The bar graphs in Figure 8 represent the conductivity of the fibers of Comparative Example 1, Example 2, Example 3, and Example 1 from left to right. The conductivity of the copper-plated single fiber increases significantly after annealing. As the annealing temperature increases, the conductivity of the copper-plated single fiber increases significantly first, and then increases slowly. When the annealing temperature reaches 400°C, the conductivity of the copper-plated single fiber increases sharply, and the conductivity increases from 1.07 × 103 S / cm to 58.3 × 103S / cm. The surface morphology of the copper layer is rough before annealing, and the surface smoothness of the copper layer is significantly improved after annealing. The surface structure of the copper layer changes from rough and porous to smooth and uniform. There are obvious gaps between copper particles before annealing, resulting in a higher contact resistance at the interface of copper particles. Therefore, the conductivity of copper-plated carbon fiber is not significantly improved compared with carbon fiber. After annealing the copper-plated carbon fiber, the copper layer becomes more uniform and dense, and the copper particles are connected to each other, which greatly reduces the contact resistance between copper particles and effectively increases the conduction path of electrons, thereby making the conductivity of copper-plated carbon fiber qualitatively improved. In addition to reducing the defects of the microstructure of the copper layer, annealing can also lead to recrystallization and grain growth of the copper layer, thereby reducing the scattering effect of the grain boundary on electrons, thereby improving the conductivity of the copper-plated carbon fiber. With the further increase of the annealing temperature to 600℃, the conductivity is significantly increased to 84.2×103S / cm, which is due to the further reduction of defects, the enhancement of the crystallinity of the copper layer and the continuous occurrence of grain boundary annihilation.

[0070] FIG9 is a bar graph showing the strength and modulus of the ablated carbon fiber (1) of Example 1, the copper-plated carbon fiber (2) of Comparative Example 1, the high-conductivity and high-strength copper-plated carbon fiber (3) of Example 2, the high-conductivity and high-strength copper-plated carbon fiber (4) of Example 3, and the high-conductivity and high-strength copper-plated carbon fiber (5) of Example 1. Compared with oxidized carbon fiber, the mechanical properties of carbon fiber after copper plating are significantly reduced. The single fiber strength of carbon fiber is reduced from 4.20GPa to 2.14GPa, and the modulus is reduced from 238.40GPa to 123.58GPa. The main reason for the reduction in mechanical properties is the low strength of copper, which reduces the mechanical properties of the overall composite fiber. However, after annealing the copper-plated carbon fiber, the mechanical properties of the fiber are improved. Taking Example 1 as an example, the single fiber strength and modulus of the copper-plated carbon fiber are increased from 2.14GPa and 123.58GPa in the unannealed state to 2.98GPa and 147.22GPa annealed at 600℃, respectively. The increase in mechanical properties is due to the reduction of surface defects in the copper layer after annealing, and the grain boundaries promote the healing of holes in the copper layer during movement. The reduction of these defects reduces the stress concentration point of the copper layer, so that the strength of copper is improved, thereby improving the mechanical properties of the overall composite fiber.

[0071] Figure 10 shows the stress-strain curves of the ablated carbon fiber (Oxidized CF) of Example 1, the copper-plated carbon fiber (CF-Cu) of Comparative Example 1, the high-conductivity and high-strength copper-plated carbon fiber (400°C) of Example 2, the high-conductivity and high-strength copper-plated carbon fiber (500°C) of Example 3, and the high-conductivity and high-strength copper-plated carbon fiber (600°C) of Example 1. It can be seen that all types of carbon fibers show elastic deformation under low strain (less than 2), which is a brittle fracture. The stress-strain curve of the high-conductivity and high-strength copper-plated carbon fiber obtained in Example 1 is closest to the ablated carbon fiber, indicating that the copper plating process of Example 1 has the least effect on the ablated carbon fiber.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high-conductivity and high-strength copper-plated carbon fiber, characterized in that: The following steps are involved: 1) ablating the polyacrylonitrile-based carbon fiber at 500° C. for 20 min, washing, and drying to obtain surface-oxidized carbon fiber; 2) adding copper sulfate, sodium citrate, sodium tartrate and sodium dodecyl sulfate into water to prepare an electroplating solution, wherein the concentration of copper sulfate is 50 g / L, the concentration of sodium citrate is 80 g / L, the concentration of sodium tartrate is 5 g / L and the concentration of sodium dodecyl sulfate is 0.6 g / L; 3) The carbon fiber oxidized on the surface of step 1) is used as a cathode, and a copper sheet with a size of 80×20×1 mm is used as an anode, and electroplating is performed in the electroplating solution prepared in step 2), the electroplating solution temperature is 60° C., the electroplating voltage is 8V, and after electroplating for ten minutes, the electroplated carbon fiber is washed with deionized water until it is neutral, and dried in a vacuum oven at 60° C. for 4 hours to obtain copper-plated carbon fiber; 4) The copper-plated carbon fiber obtained in step 3) is heated to 400° C. at 8° C. / min and annealed for 15 min under nitrogen protection, and then cooled to obtain high-conductivity and high-strength copper-plated carbon fiber.

Citation Information

Patent Citations

  • Carbon fiber facric and manufacturing method thereof

    KR1020190088319A